2018
DOI: 10.4314/jasem.v22i6.15
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of crude oil induced alteration of oxidative stress indices in rat by red palm oil

Abstract: The toxic properties of crude oil were hitherto described. Therefore, several materials are being tested for protective potential counter to petroleum toxicity. This study evaluated the oxidative stress status of rats fed diet incorporating petroleum tainted diet with red palm oil. Four groups with six rats in each group were employed in this study. Rats in group 1 were fed with fish feed only while rats in group 2 were fed with crude oil tainted diet and rats in groups 3 and 4 were fed with contaminated feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…These results are in agreement with results reported by Kayode Chidimma and Alwell (). A crude oil‐tainted diet stimulated lipid peroxidation and caused a decline in reduced glutathione levels, superoxide dismutase and catalase activities (Achuba, ). Alisi, Ojiako, Osuagwu, and Onyeze () reported that oxidative stress is the primary mode of action of crude oil‐induced renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with results reported by Kayode Chidimma and Alwell (). A crude oil‐tainted diet stimulated lipid peroxidation and caused a decline in reduced glutathione levels, superoxide dismutase and catalase activities (Achuba, ). Alisi, Ojiako, Osuagwu, and Onyeze () reported that oxidative stress is the primary mode of action of crude oil‐induced renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…All of the above are similar to the protection conferred on rats by incorporation of powdered oil palm leaf in petroleum-contaminated diets in rats by Achuba. 26; 27 In another development, crude oil diet contamination is often occasioned with the generation of oxidative radicals which is often culminated in the depletion of several enzymatic and non-enzymatic antioxidants and increased lipid peroxidation 6,14,18,19,[25][26][27] and is said to be no different from the one reported in this study (Table 5). However, the use of plant materials by various studies have also been reported to contribute significantly to averting the free radical generating potentials of crude oil-induced oxidative damage to animals.…”
Section: Resultsmentioning
confidence: 84%
“…[6][7][8] This trend makes food chain petroleum contamination a high-risk burden in areas where ever crude oil exploration occurs as the breakdown of petroleum hydrocarbons have led to the release of free radical generating compounds and activated oxygen, nitrogen, hydrogen, and carbon metabolites into the cells leading to different types of autoimmune disease conditions often manifested as growth impairment, oxidative stress, diabetes, neurodegeneration, and cancer. [9][10][11][12][13][14] In a bid to come to the rescue of man, researchers' all over the world have increasingly advocated the use of natural products as alternatives to synthetic adjuvants against toxic compounds as these synthetics aside being expensive may have some element of contribution to counter drug reactions occurring in biological systems. [15][16][17] Some of the most recent adjuvants used include Vernonia amygdalina extracts, [18][19][20] Monodora myristica extracts, [21][22][23] Moringa oleifera extracts, 24,25 © 2020 the authors.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical consequences of consuming hydrocarbon tainted diet have been voraciously reported [11,37,38,39,40]. Moreover, one major health implication of exposure to crude petroleum is decrease in body weight [4].…”
Section: Resultsmentioning
confidence: 99%